História, literatura e imprensa: as revoluções liberais e o romance O Último Homem (1826) de Mary W. Shelley - Barros, Pedro Henrique Rodrigues (2022)
This dissertation intends to investigate how Mary W. Shelley, a woman and writer at the beginning of the 19th century, approached the theme of liberal revolutions in the book The Last Man, published in 1826. The proposal is to understand how the author experienced and then interpreted the revolutionary processes taking place in Europe in his fictional work, making literature a space to debate and intervene in the world of which he was a part. From the analysis of Mary W. Shelley's novel and letters, it is possible to verify that the writer was constantly attentive to the debates about the liberal revolutions that then emerged in different parts of the world: Italy, Spain, Greece and some Latin American countries. . Through news published in the British press at the time, the writer experienced discussions about the causes and consequences of such political events. Based on this observation, in this work we analyze the interlocution between novels, letters and the press regarding the theme of the revolutions that marked the first decades of the 19th century in Europe. Through the reading of articles and reports published in the English press about the Greek Revolution, the central theme of the novel The Last Man, we try to understand what social readings and interpretations the author made of the event and the way in which she transformed it into the element of her work. We argue in this work that there are indications that Shelley used the metaphor of a social illness – represented in the novel as an epidemic/plague that exterminates humanity – caused by political despotism. In the midst of the results of the Congress of Vienna (1815) and an advance of conservative ideas among European states, the author, through her novel, seemed to criticize despotism, pointing out its harmful effects and warning about the revolutionary clamor that then imposed it if as an answer.